Synthesis and Spectroscopic Investigations of Coordination Compounds of Mo(VI) with Thiourea - Pathak, Vishal; Srivastava, B.K. (Asian Journal of Chemistry, 2010)
In continuation of our earlier work on Cr(III) and V(V) complexes with thiourea, Mo(VI). complexes of thiourea were synthesised at different pH. The complexes were soluble in water but insoluble in common organic solvents like ethanol, acetone and carbon disulphide. Their structural features have been investigated on the basis of elemental analysis, IR spectra, 1H-NMR and 13C NMR spectra, which confirm their octahedral structures.